2019
DOI: 10.1088/1755-1315/269/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

PrimaTourism: Plant selection by Schlegel’s Banded Langur Presbytis neglectus in Johor

Abstract: Schlegel’s Banded Langur, P. neglectus is an understudied primate species in Johor. However, no data were recorded on the species feeding ecology from previous study. This study aims to assess the food selection of P. neglectus in Kampung Johor Lama, Kota Tinggi, Johor. Observations were made using scan sampling techniques and identification of plants was made using dichotomous key to record and identify the plants eaten by P. neglectus in Kampung Johor Lama, Kota Tinggi, Johor. 27 species of plants were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Habitat quality may also affect dietary diversity ( Mohd-Daut et al 2021 , Mohd-Daut and Md-Zain 2021 ). Primates living in undisturbed forests with greater tree species diversity have more foraging options and are less likely to experience food scarcity than primates living in more fragmented forests ( Poulsen et al 2001 , Najmuddin et al 2019 , Najmuddin et al 2021 ). Intraspecific comparisons of the proportion of plant food resources in different primate groups living in habitats with varying disturbance levels are one technique for investigating how these species respond to human habitat alteration and dietary adjustments ( Wieczkowski 2003 , McLennan et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Habitat quality may also affect dietary diversity ( Mohd-Daut et al 2021 , Mohd-Daut and Md-Zain 2021 ). Primates living in undisturbed forests with greater tree species diversity have more foraging options and are less likely to experience food scarcity than primates living in more fragmented forests ( Poulsen et al 2001 , Najmuddin et al 2019 , Najmuddin et al 2021 ). Intraspecific comparisons of the proportion of plant food resources in different primate groups living in habitats with varying disturbance levels are one technique for investigating how these species respond to human habitat alteration and dietary adjustments ( Wieczkowski 2003 , McLennan et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reforestation of our study area with non-commodity plants preferred by P. femoralis could serve as a buffer between the forest and other crops and, as a result, reduce their crop-raiding. Promoting ecotourism, and specifically ‘PrimaTourism’ (a term referring to primate-based tourism) (Najmuddin et al 2019a), at the study site along with broader conservation education programmes may also help increase both income to villagers and awareness for P. femoralis . This type of tourism and education has succeeded in protecting other colobines (e.g., Lhota et al 2019a, Lhota et al 2019b) and thus provides a useful tool for protecting P. femoralis as well.…”
Section: Discussionmentioning
confidence: 99%
“…This habitat allows daytime observations of the monkeys on foot. Consequently, authors of other studies have reported the population distribution, activity budget and predation threats of P. femoralis at this study site (Abdul-Latiff et al 2019a, Najmuddin et al 2020, Najmuddin et al 2019a, Najmuddin et al 2019b), though knowledge about the feeding ecology of P. femoralis is incomplete. Thus, this study aimed to describe P. femoralis dietary habits and discuss the interactions between their feeding behaviour and their surroundings.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Generally, P. femoralis are herbivores but also consume fruits and seeds as well (Caton, 1990;Nijboer, 2006;Kirkpatrick, 2017). Based on preliminary study on the P. femoralis, it can forage up to 27 species of plants from 17 families in severely fragmented habitat in Johor (Najmuddin et al, 2019a). in their preliminary study using ad libitum observation method had found the P. femoralis spending 36.85% of their activity budget resting, followed by moving (35.65%) and feeding (21.79%) 2019c).…”
Section: Introductionmentioning
confidence: 99%